On Mathematical Model for the Study of Traffic Flow on the High Ways - Fadugba, Sunday Emmanuel; Okunlola, Joseph Temitayo; Ajayi, Adedoyin Olayinka; Edogbanya, Olaronke Helen (International Journal of Mathematical Research, 2014)
This paper presents mathematical model for the study of traffic flow on the highways. The effect of the density of cars on the overall interactions of the vehicles along a given distance of the road was investigated. We also observed that the density of cars per mile affects the net rate of interaction between them.